(untitled) (Bangladesh Medical Journal, 2019)
Burn causes both the physical and psychological trauma of the victims. Most of the cases, physical trauma of burn are highlighted and managed but psychological impacts of burn are ignored. The psychological aspects of burn injury have been researched in different parts of world producing different outcomes. A very few number of study regarding psychological aspect of burn has been conducted in our country till now. To assess the psychiatric morbidity among the burn patients admitted in burn unit of Dhaka Medical College Hospital. This was a descriptive and analytical study. The study was conducted in the Burn and Plastic Surgery Unit of Dhaka Medical College Hospital, Dhaka, Bangladesh and the duration of the study was 6 (six) months (July 2010 - December 2010). Burned patients fulfilling the inclusion criteria. 124 patients were selected on non-probability purposive sampling techniques who were GHQ (General Health Questionnaire) positive. Then a semi-structured questionnaire containing socio-demographic characteristics and SCID-I (Structured Clinical Interview for DSM-IV Axis-I disorder) was used. Finally DSM-IV-TR criteria were used among burn patients clinically. Different types of psychiatric morbidity in post burn patients and different burn related factors affecting psychiatric outcomes were assessed. The psychiatric morbidity among the burn patients was 47.6%. Regarding patterns of psychiatric morbidities, the highest number of patients were anxiety disorder (54%) followed by depressive disorder 36%, acute stress disorder (ASD) 3%, post traumatic stress disorder (PTSD) 5% and 2% psychotic disorder.The burned patients of low socioeconomic condition, less education, unmarried, suicidal attempted and larger total body surface area (TBSA) were found their multiple sites of burn injuries (like head, neck and face) developed psychiatric disorders. This study highlights the importance of the simultaneous evaluation and management of psychiatric disorders in burn injured patients. Management of phychiatric and phychological problems of burned patients would bring better outcome. Bangladesh Med J. 2019 Jan; 48 (1): 18-25